Pengaruh Lifestyle Adaption dan Social Media Influence Terhadap Willingness to Buy Healthy Food - Ritchie Etenia Lucianto; Eryd Saputra; Miratia Afriani; Arina Luthfini Lubis (Ridwan Institute, 2025)
This study aims to analyze the effect of lifestyle adaptation and social media influence on willingness to buy healthy food among the people of Batam City. The increasing awareness of healthy lifestyles and the significant role of social media in shaping consumer behavior form the main background of this research. A quantitative explanatory approach was employed, and data were collected through questionnaires distributed to 180 respondents who had consumed healthy food products and were active social media users. The data were analyzed using multiple linear regression with the assistance of SPSS version 26. The results indicate that both lifestyle adaptation and social media influence have a positive and significant effect on willingness to buy healthy food. The coefficient of determination (R²) value of 0.849 shows that 84.9% of the variation in willingness to buy healthy food can be explained by the two independent variables. Among them, social media influence has a more dominant effect than lifestyle adaptation. These findings suggest that consumers’ willingness to purchase healthy food is driven not only by their awareness of a healthy lifestyle but also by exposure to digital information, promotions, and social media campaigns. The results of this study are expected to serve as a reference for business practitioners and policymakers in designing effective marketing communication strategies to increase healthy food consumption among the public.